Alcohol use disorder manifestations and screening - Jankowska, Paula; Jankowski, Krzysztof; Rudnicka-Drożak, Ewa (Journal of Education, Health and Sport, 2018)
IntroductionAlcohol use disorder is a very common problem in many societies. It produces vast problems in the area of health of individuals, relations in families, public healthcare costs and danger to other community members. In Poland, 11.9% of Polish residents can be included in the general category of alcohol abusers, in which 2.4% of people meet the diagnostic criteria for alcohol addiction. Thus, even every family doctor meets in his practice patients who drink alcohol excessively and identification of patient suffering from alcohol-related problems is crucial as simple interventions are very effective.ObjectiveTo present methods of assessment and screening for alcohol use disorder.ResultsScreening for alcohol use disorder is complex process. Family doctor should carefully look for such symptoms as bloodshot eyes, reddish, swollen face with dilated facial capillaries and hand and tongue tremor. Patients may report some social problems. Laboratory tests may reveal elevated aspartate gamma glutamyl transferase levels and raised mean cell volume. Apart from clinical assessment, general practitioner should use standardized questionnaires like AUDIT, AUDIT-C, CAGE or MAST to identify patients with alcohol use disorder,ConclusionsThe problem of excessive alcohol consumption is very common in the primary care. Assessment of alcohol use disorder occurrence in patient is absolutely important and should be multifarious. General practitioner should perform careful physical examination and history taking, as some symptoms and signs may be indicators of problems with drinking alcohol. Obtaining results of simple laboratory tests can be a diagnostic tip as well. Screening also involves use of diagnostic instruments, preferably AUDIT (or AUDIT-C) or MAST, CAGE tools.